Relasi Makna Sinonimi Adjektiva Waktu dalam Bahasa Indonesia - Febriani, Elya; Aliurridha, Aliurridha; Ikomah, Rinda WidyA (Ruang Kata, 2025)
This study discusses the meaning relations of synonymous pairs of Indonesian time adjectives using synonymy theory in the realm of lexical semantics. The meaning relations between synonymous words are not absolute. In certain contexts, synonymous words can be used interchangeably, but in other contexts they cannot be used interchangeably. Therefore, this study attempts to identify the distribution of patterns of use of synonymous pairs of time adjectives and what aspects differentiate the meanings of words in synonymous pairs of time adjectives. The purpose of this study is to prove the existence of differences in meaning between synonymous pairs. Data in this study were obtained from newspapers, e-books of short stories, dictionaries, and based on the researcher's linguistic intuition. This study applies a descriptive analysis method with a qualitative approach. The data collection method in this study uses the listening method with the reading and note-taking technique. Data analysis uses Simak method with the direct element sharing technique and the substitution technique. The results show that word pairs have different distributions and in certain contexts their use cannot be interchanged. This is possible because there are differences in meaning caused by differences in implications, applications, one meaning being more general than the other, taste values and differences in the variety of usage